The Impact of Order and Mode of Market Entry on Profitability and Market Share - Pan, Yigang; Li, Shaomin; Tse, David K. (Journal of International Business Studies, 1999)
Market share performance and profitability of overseas business activities has long been an important issue in international business. In this study, we explore the impact of order and mode of market entry into an overseas market. We find that early entrants have significantly higher market shares and profitability than late followers. We also find that equity joint ventures have a higher profitability than either wholly owned operations or contractual joint ventures. A significant interaction exists between order and mode of market entry. As expected, firm efficiency and size affect the performance of firms. These results are based on the business activities of a sample of 14,466 foreign firms in China in 1995.